Penerapan Algoritma Pencarian Knuth-Morris-Pratt dalam Sistem Informasi Perpustakaan pada SMAN 1 Babelan - Diti , Nur Azizah; Khasanah , Fata Nidaul; Fitriyani , Aida (Journal of Students‘ Research in Computer Science, 2022)
The library is a place where information can be obtained easily. Because in the library there are lots of books, journals, and research results that can be used. As is the case in the library of SMAN 1 Babelan. But in fact the library of SMAN 1 Babelan still has not implemented a digital technology information system. So that in the recording process, they still use a manual system or recording in a ledger. Therefore, a system is needed to overcome this problem by implementing the Knuth-Morris-Pratt algorithm which is a string search algorithm, and the Waterfall search development method.